The results of the comparative evaluation of samples of oat (A. sativa L., A. byzantine C. Koch) for resistance to lodging, yield and adaptability in central Non-chernozem zone of the Russian Federation - Julia I. Vargach (Овощи России, 2019)
Relevance. Each sample is characterized by a number of biological features, due to the recombination of genetic material in the process of its selection. These features are manifested in the reaction of plants to soil-climatic and technological conditions, expressed in the change of the elements of the yield structure and indicators of the level of adaptability of plants to growing conditions, as well as resistance to lodging. New samples have little-known properties that need to be studied and compared in specific soil and climatic conditions, to assess them in order to decide on the possibility of their zoning or culling. The main indicators characterizing the level of agricultural production are productivity, resistance to lodging, since the shortage of grain as a result of lodging of cereals can reach 15-40%. The introduction of new high-yielding varieties on the basis of their testing and the use of the most effective technological methods of cultivation on crops will allow to receive a significant gross harvest.Materials and methods. The study was carried out in 2016-2018 to assess models of cultural hexaploid species of oats hulled and naked forms of resistance to lodging, yield and adaptability in the temperate continental climate of Central non-Chernozem zone. Resistance to lodging, yield variability, indices of environmental conditions and adaptability were determined. The main method of evaluation of the field resistance to lodging – visual (in points) that allows you to rank the varieties based on this characteristic. We were calculated potential productivity and adaptability of varieties by method L. A. Zhivotkov et al. [1], an indicator of the stability level of the sample yield (Puss) by the method of E. D. Nettevich et al. [2].Results. Many varieties showed good plasticity and high productivity potential. The best in resistance to lodging, yield and adaptability among the hulled forms were varieties Sig, Mirt, Poseidon, Belinda, Rajtar, and the naked forms – Becas, Vyatsky, Korolek.